Moderate phosphorus additions consistently affect community composition of arbuscular mycorrhizal fungi in tropical montane forests in southern Ecuador - Dueñas, Juan F (The New phytologist, 2020)
©2020 The Authors. New Phytologist ©2020 New Phytologist Trust.